Effect of dietary Moringa oleifera on production performance and gut health in broilers - Gul, Shumaila; Hussain, Fida; Taj, Raheela; Ullah, Asad (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: In the present research work, we examined the dietary Moringa oleifera effect on gut health and growth traits in chickens. Materials and Methods: There were 280 chicks (day old) that were weighted and allotted uniformly in seven groupings, each containing eight replicates (n = 5). Birds were supplemented with M. oleifera leaf extract (MLE) and seed extract (MSE) for 35 days. Group I was the control (fed merely basal diets), while Group II received 0.8% MLE, Group III was given 0.8% MSE, Group IV was given 1.2% MLE, Group V was given 1.2% MSE, Group VI was given 0.8% MLE + 0.8% MSE, and Group VII was given 1.2% MLE + 1.2% MSE. At the end of the fifth week, two chickens were selected from each replica, and samples (small intestine and ileal ingesta) were collected. Results: The chicken diet with MLE and MSE supplements saw significant improvement (p < 0.05) in both feed conversion ratio (FCR) and body weight gain (BWG). In the small intestine (duodenal, jejunal, and ileal), dietary MLE and MSE supplements significantly increased (p < 0.05) the surface area of the villus and the ratio of their height/crypt depth in comparison to the control group. The MLE and MSE supplements significantly increased (p < 0.05) the total goblet cell counts in the small intestine. The Lactobacillus spp. count was significantly improved (p < 0.05) and reduced (p < 0.05) in Escherichia coli counts when the bird diet was supplemented with MLE (0.8%) and MSE (0.8%). Conclusion: Results indicated that M. oleifera leaf and seed extract diet improved the growth trait and gut health in chickens. Adv. Vet. Anim. Res., 11(2): 339-348, June 2024 http://doi.org/10.5455/javar.2024.k782